Atomic Sn–enabled high-utilization, large-capacity, and long-life Na anode - Xu, Fei; Qu, Changzhen; Lu, Qiongqiong; Meng, Jiashen; Zhang, Xiuhai; Xu, Xiaosa; Qiu, Yuqian; Ding, Baichuan; Yang, Jiaying; Cao, Fengren; Yang, Penghui; Jiang, Guangshen; et al. (Science Advances, 2022)
Constructing robust nucleation sites with an ultrafine size in a confined environment is essential toward simultaneously achieving superior utilization, high capacity, and long-term durability in Na metal-based energy storage, yet remains largely unexplored. Here, we report a previously unexplored design of spatially confined atomic Sn in hollow carbon spheres for homogeneous nucleation and dendrite-free growth. The designed architecture maximizes Sn utilization, prevents agglomeration, mitigates volume variation, and allows complete alloying-dealloying with high-affinity Sn as persistent nucleation sites, contrary to conventional spatially exposed large-size ones without dealloying. Thus, conformal deposition is achieved, rendering an exceptional capacity of 16 mAh cm−2 in half-cells and long cycling over 7000 hours in symmetric cells. Moreover, the well-known paradox is surmounted, delivering record-high Na utilization (e.g., 85%) and large capacity (e.g., 8 mAh cm−2) while maintaining extraordinary durability over 5000 hours, representing an important breakthrough for stabilizing Na anode.
CRIS-Team Scopus Importer:2023-03-20